Kualitas dan Kuantitas Sperma Kambing Bligon Jantan yang Diberi Pakan Rumput Gajah dengan Suplementasi Tepung Darah (Quality and Quantity of Semen of Buck Bligon Fed Elephant Grass Supplemented with Blood Meal). - Agustinus Agung Dethan; Kustono (Kustono); Hari Hartadi (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The experiment was conducted to determine the quality and quantity of semen of buck Bligon fed elephant grass supplemented with blood meal. The experiment was carried out in Laboratory of Animal Physiology and Reproduction,Faculty of Animal Science, Universitas Gadjah Mada, Yogyakarta. Nine bucks Bligon age 8 to 12 months were used in the experiment. The experimental animals were devided into three groups of feed treatment, i.e group 1 (R0); elephant grass (60%) + corn meal (15%) + rice bran (15%) + soybean cake (10%), group 2 (R1); elephant grass (60%) + corn meal (15%) + rice bran (15%) + soybean cake (5%) + blood meal (5%), group 3 (R2); elephant grass (60%) + corn meal (15%) + rice bran (15%) + blood meal (10%). The experiment was carried out for 3 months. Semen collection using artificial vagina was done two times a week for four weeks. The variables measured were semen volume, semen pH, sperm motility, sperm consentration, sperm viability, and sperm abnormality. The experiment data were statisticaly analyzed using completely randomized design using statistical analysis and then continued with Duncan test to analyze the differences between means. The results showed that the suplementation of blood meal significantly increased (P≤0.01) semen volume. Semen volume for R0 was 0.42 ml lower than R1 0.82 ml and R2 0.69 ml whereas R1 and R2 differed significantly (P≤0.05). The treatments have significant effect (P≤0.01) on sperm motility. The highest spermmotility value was at treatment R1 which was 84.17% followed by R2 81.67% and the lowest was R0 65.00%. The effect of treatment on sperm concentration also significant (P≤0.01). Sperm concentration of R1 was 5,537.67 million cell/mlsemen and R2 was 4,415.33 million cell/ml semen which were higher than R0 (3,081.00 million cell/ml semen). Viability was significantly affected (P≤0.01) by the treatments. Viability value at treatment R0 was 69.88% and for treatment R1 and R2 were 91.25% and 87.63% respectively, the values differed significantly (P≤0.05). The effect of treatment on pH semen and sperm abnormality was not significant. Feed containing blood meal, corn meal, rice bran, and soybeancould increase the quality and quantity buck Bligon semen. The improvement of local goat livestock productivity could be done by giving blood meal as an alternative of protein source for feed supplement, particularly at areas having lowquality feed.(Key words : Goat, Semen quality, Blood meal)